1965
DOI: 10.1002/polc.5070110120
|View full text |Cite
|
Sign up to set email alerts
|

The optical rotation of wood xylans

Abstract: Previously derived equations relating the specific rotation and chemical composition of 4‐O‐methylghicurono‐xylans and arabino‐4‐O‐methylglucurono‐xylans have been found to be partly incorrect because of the assignment of an erroneous value to the rotatory contribution of the 4‐O‐methyl‐α‐D‐glucuronosyl xylose residue. The correct value was calculated from the known molar rotations of xylobiose and 22‐(4‐O‐methyl‐α‐D‐glucuronosyl) xylotriose. Approximately the same values were obtained from the specific rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The specific optical rotation of extracted xylan matches well with the commercial xylan and confirms that the extracted xylan is composed of α-linked d -glucuronic acid and β-linked d -xylose monosugar. Similar results for different xylans extracted from wood were reported by Gutmann and Timell . The elemental composition analysis of extracted xylan showed that it contains 36.70% carbon content and 3.92% hydrogen content, while the nitrogen and sulfur content are absent in the extracted xylan, confirming that the extracted xylan is highly pure.…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The specific optical rotation of extracted xylan matches well with the commercial xylan and confirms that the extracted xylan is composed of α-linked d -glucuronic acid and β-linked d -xylose monosugar. Similar results for different xylans extracted from wood were reported by Gutmann and Timell . The elemental composition analysis of extracted xylan showed that it contains 36.70% carbon content and 3.92% hydrogen content, while the nitrogen and sulfur content are absent in the extracted xylan, confirming that the extracted xylan is highly pure.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Similar results for different xylans extracted from wood were reported by Gutmann and Timell. 29 The elemental composition analysis of extracted xylan showed that it contains 36.70% carbon content and 3.92% hydrogen content, while the nitrogen and sulfur content are absent in the extracted xylan, confirming that the extracted xylan is highly pure.…”
Section: Resultsmentioning
confidence: 87%
“…One would therefore expect, on this model, to find carrier mobilities in polymers increasing with molecular weight. Such an effect has been predicted by Gutmann 38 on the basis of a computer study of residual long-range order in polymers. He finds that the spatial extent of such order is proportional to (molecular weight)* and proposes the formation of energy bands which, although fairly wide, are localized in both space and time.…”
Section: Results a N D Discussionmentioning
confidence: 79%